Effects of a single bout of moderate-to-vigorous physical activity on executive functions in children with attention-deficit/hyperactivity disorder: A systematic review and meta-analysis. (January 2022) - Chueh, Ting-Yu; Hsieh, Shu-Shih; Tsai, Yu-Jung; Yu, Chien-Lin; Hung, Chiao-Ling; Benzing, Valentin; Schmidt, Mirko; Chang, Yu-Kai; Hillman, Charles H.; Hung, Tsung-Min
Abstract: Objectives: The aim of this study was to systematically review the literature investigating the acute effects of moderate-to-vigorous physical activity (MVPA) on executive functions (EFs) in children with attention-deficit/hyperactivity disorder (ADHD) and perform a meta-analysis of the effects of MVPA on task components that require lower and higher EF demand in this population. Methods: The systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Six electronic databases, i.e., PubMed, Scopus, Web of Science, Embase, SPORTDiscus, and Education Resources Information Center (ERIC), were searched for eligible studies. Random-effects weights were used to pool the effect sizes. Publication bias was assessed by Egger's regression test and Rosenthal's fail-safe N . This study is registered on PROSPERO, number CRD42020184082. Results: The electronic database search yielded 12 studies, which met the inclusion criteria, comprising a total of 375 participants. Eleven studies with data from 275 participants were included in the meta-analysis to examine the acute effects of MVPA on tasks with lower and higher EF demand. A single bout of MVPA had a small positive effect on tasks with lower ( n  = 10, g  = 0.32, 95% CI = 0.123–0.517) and higher ( n  = 10, g  = 0.25, 95% CI = 0.13–0.371) EF demand. No publication bias was found. Conclusions: A single bout of MVPA may have a general facilitative effect on cognition, indicating that acute MVPA may be a transient nonpharmacological adjunctive treatment for childhood ADHD. Highlights: Children with attention-deficit/hyperactivity disorder exhibit cognitive deficits in executive functions, which affects their daily functioning. A single bout of moderate-to-vigorous physical activity has a general facilitative effect on cognition in these children. The literature suggests that a single bout of 15–30 min of moderate-to-vigorous physical activity is a feasible approach to temporarily facilitate executive functions in children with attention-deficit/hyperactivity disorder.